Trends in treatment outcome of smear-positive pulmonary tuberculosis in Southeastern Nigeria, 1999 - 2008 (Italian Journal of Public Health, 2012)
Background: the Directly Observed Treatment Short Course (DOTS) strategy was introduced into the tuberculosis control programme of Ebonyi, Southeastern, Nigeria in 1996. The impact of the programme on the treatment outcomes for smear-positive tuberculosis has not been assessed ever since. We assessed the trends in treatment outcome for new smear-positive pulmonary tuberculosis between 1999 and 2008.Methods: we conducted a retrospective analysis of the Ebonyi state Ministry of Health quarterly smear-positive tuberculosis statistical returns. Patients were treated and treatment outcome categories computed according to the WHO/National Tuberculosis Control Programme’s guidelines. Chi-square for trends was used to determine significance.Results: the number of smear-positive cases who registered for treatment fell from 1 361 patients in 1999 to 977 in 2008 (Trend χ2=349; P
Keywords: Tuberculosis; Smear-positive; Treatment outcome; DOTS; Tuberculosis control; Nigeria